The Internet, The Cloud, and Information Technology Governance - Asgarkhani, Mehdi; Bartlett, Christopher; Bracken, Dave (International Journal for Applied Information Management, 2021)
Information Technology Governance (ITG) has become a catalyst for strategic evaluation and deployment of IT solutions. Much of the concepts, the mechanisms, the processes, the frameworks, and the standards of ITG date back to the 1990s. A review of recent studies indicates an increased uptake of ITG practices within organizations – mostly via the adoption of ITG standards and frameworks. Within the last decade, we have witnessed rapid technological advancements which have in turn motivated radical changes in the management of IT infrastructure, deployment of IT applications, and delivery of IT services. For instance, Data Centers and Cloud Services have transformed the paradigm of infrastructure and application management in the IT sector. Moreover, sophisticated smart mobile solutions have made it possible to develop IoT solutions enabling smart cities and smart building initiatives. A review of timelines when ITG concepts and standards established suggest that they originated years before recent transformations in technology adoption took place. Some ITG standards show that the adoption of some cloud services motivated revision in some ITG frameworks. This study demonstrates that there is a possibility that some of the current ITG standards are not fine-tuned to reflect recent developments in the adoption of IT solutions and services.